(untitled) (Journal of Hama University, 2020)
This search depends on the basic idea that the human communication doesn’t stop at borders of spoken words, it goes beyond that to include the movements of the body and its organs as face, eye, limbs and the body posture. So, gestures of glumness, frown, smile and movements of body, are represented in Al-Aghriba through poetry artistic expressive imagery that have communicative and emotional perspectives. Their importance might also lie in their ability to translate the whispers of the soul and showing them on external parts of the human body unconsciously. Thus constituting an important factor in the process of "Humman Commuication". This research attempts to reveal how the emotional expressive imagery of the eye are used as a poetic component in the poetry of Al-Aghriba among the pre-Islamic and veterans, as it aims to reveal the concept of the beauty performed by the gestural imaging of the eye. On the other hand, the importance of research is evident in the poetic employment of gestural discourse and the emotions of the eye and its effect in forming a poetic discourse that addresses the feelings of the recipient and arouses his emotions, discovering the aesthetic perspectives with their poetic manifestations, explaining the relationship between emotion and its manifestation in eye movements, and studying the language of the eye according to the concept of beauty. Novelty in this research lies in the poetic employment of eye expression and building a poetic imagery that has psychological and technical properties of "Al-Aghriba poetics".It also contributes in discovering the relations of temporal and spatial environment to the characteristics of poetic discourse and supplies us with historical features of poetic discourse imagery of eye’s language, It clearly points to creative elements of " Al-Aghriba Poets phenomena".